Factors Influencing The Involvement Of Malaysian Youths In Massively Multiplayer Online Role-Playing Games (MMORPGs) - Mohd Yunus, Yuza Haiqal; Yusoff, Nur Hafizah; Ng , Cai Yan (Journal of Techno-Social, 2021)
Massively multiplayer online role-playing games (MMORPGs) is an online game that requires a massive number of players that interact to one another in a virtual world. The combination of role-playing video games and massively multiplayer online games that enable youth to interact in virtual world has made this game as one of the most popular online games in this era. This study focused on factors that influence the youth in MMORPGs. The main focus of this quantitative study is the youth at the range of 15 to 30 years old who actively play online games through Facebook by using purposive sampling method. A total of 50 respondents were willingly answered the questionnaire and duration to complete the survey was around one month. From the result, this study shows that there are two factors which are internal and external factors that influence the participation in MMORGPs among youth. Stress reliever, excitement, addiction, source of income and the attempt to escape from reality are some internal factors that influence youth to involve themselves in MMORGPs. As for the external factor, this study found that social influences such as social interaction, social control and mass media had played a huge role. The findings of this study can be used as a future reference for in-depth studies that should focus more on the effects of involvement of youth in MMORGPs.